A clinician's brief guide to dementia and the law - Brindle, Nick ca. 20./21. Jh (Cambridge medicine (Series), 2023)
Dementia is a topic of enormous medical, legal and ethical importance with considerable human and economic cost. Its importance grows with the change in demographics of the aging population and that people with dementia receive care in a wide range of settings. The legal and ethical problems raised in treating patients with dementia are diverse and complex and are dealt with by many practitioners on a daily basis. This book is a 'how-to' guide to understanding how the law applies to people with dementia, from diagnosis through to end-of-life. It explores the practical problems that people experience, and practitioners face, giving an accurate account of statute, court cases and other inquiries, to give readers an up-to-date account of the law and how it applies in this area. An essential read for clinicians and practitioners that work with patients with dementia, including psychiatrists, primary care physicians, nurses, social workers and advocates